Preparation of Tetrabenzo[4.4.2]undecastarphene by On‐Surface Synthesis. Issue 7 (29th April 2021) - Jancarik, Andrej; Khanh Hung, Nguyen; Skidin, Dmitry; Moresco, Francesca; Gourdon, Andre
Abstract: A large dissymmetric starphene molecule, the tetrabenzo[ a, c, u, w ]naphtho[2, 3‐ l ]nonaphene, was obtained by first preparing a soluble precursor which was then sublimated on a Au(111) surface in an ultra‐high vacuum. In a second step, controlled annealings from 200 °C to 275 °C initiated two successive cyclodehydrogenation steps with the formation of 3 new carbon‐carbon bonds. A second conformer was also stable enough during the annealing step to give another compound in similar yield, the benzodibenzo[7, 8, 9, 10]naphthaceno[2, 1‐ h ]phenanthro[9, 10‐ p ]hexaphene. The formation of this more‐hindered species stresses the importance of strong molecule‐surface interactions during the cyclodehydrogenations steps of these large polyaromatic hydrocarbons. Abstract : Two dissymmetric large starphene molecules, the tetrabenzo[4.4.2]undecastarphene and the benzodibenzo[7, 8, 9, 10]naphthaceno[2, 1‐h]phenanthro[9, 10‐p]hexaphene, have been obtained in the ratio 1 : 1 by successive on‐surface cyclodehydrogenation steps on a gold surface from a sterically crowded and soluble precursor. The formation of the more hindered hexaphene species stresses the importance of strong molecule‐surface interactions during the cyclodehydrogenation steps of these large polyaromatic hydrocarbons, which can be applied as single‐molecule logic gates.